Lifetime of Parahydrogen in Aqueous Solutions and Human Blood. Issue 19 (12th September 2019) - Schmidt, Andreas B.; Wörner, Jakob; Pravdivtsev, Andrey; Knecht, Stephan; Scherer, Harald; Weber, Stefan; Hennig, Jürgen; von Elverfeldt, Dominik; Hövener, Jan‐Bernd
Abstract: Molecular hydrogen has unique nuclear spin properties. Its nuclear spin isomer, para hydrogen ( p H2 ), was instrumental in the early days of quantum mechanics and allows to boost the NMR signal by several orders of magnitude. p H2‐ induced polarization (PHIP) is based on the survival of p H2 spin order in solution, yet its lifetime has not been investigated in aqueous or biological media required for in vivo applications. Herein, we report longitudinal relaxation times ( T 1 ) and lifetimes of p H2 ( τ P O C ) in methanol and water, with or without O2, NaCl, rhodium‐catalyst or human blood. Furthermore, we present a relaxation model that uses T 1 and τ P O C for more precise theoretical predictions of the H2 spin state in PHIP experiments. All measured T 1 values were in the range of 1.4–2 s and τ P O C values were of the order of 10–300 minutes. These relatively long lifetimes hold great promise for emerging in vivo implementations and applications of PHIP. Abstract : Spin relaxation : Longitudinal relaxation and para ‐to‐ ortho conversion of H2 are investigated in aqueous solutions and human whole blood. A relaxation model is proposed to simulate relaxation of the spin state of H2 . Para‐ H2 is a powerful source to enhance the signal of magnetic resonance, particularly promising for metabolic imaging and continuous hyperpolarization.